Pengaruh Pajak Daerah, Retribusi Daerah, Dana Alokasi Umum (DAU) terhadap Pertumbuhan Ekonomi Melalui Belanja Modal di Kabupaten Tanjung Jabung Timur Tahun 2007-2021 - Maryani Maryani; Zamzami Zamzami; Erni Achmad (Universitas Batanghari, 2023)
The purpose of this study is first, to determine economic growth in terms of its development in East Tanjung Jabung Regency during the 2007-2021 period; Second, to find out the effect of local taxes, regional fees, general allocation funds on capital expenditures in East Tanjung Jabung Regency for 2007-2021; Third, to determine the effect of local taxes, regional fees and general allocation funds on economic growth in East Tanjung Jabung Regency in 2007-2021; Fourth, to determine the effect of local taxes, regional fees, and general allocation funds on economic growth through capital expenditure in East Tanjung Jabung Regency in 2007-2021. In this research the research used is quantitative descriptive analysis. The data in this research is in the form of information for a specific duration (time series) for 2007-2021 in East Tanjab Regency. The analytical method used in this research is descriptive analysis and quantitative analysis in the form of path regression analysis (Path Analysis). In general, the variables of Regional Taxes, Regional Retributions, General Allocation Funds, Capital Expenditure and Economic Growth experienced positive growth on average during 2007-2021. The effect of local taxes, regional levies and the General Allocation Fund on Capital Expenditures in East Tanjung Jabung Regency for 2007-2021 simultaneously has no significant effect. The effect of regional taxes, regional levies and general allocation funds on Economic Growth in East Tanjung Jabung Regency in 2007-2021 simultaneously has a positive and significant effect. The effect of regional taxes, regional levies, general allocation funds on economic growth through capital expenditure in East Tanjung Jabung Regency for 2007-2021 simultaneously has a positive and significant effect.